Advancing Global Citizenship of Underrepresented and Hypersegregated U.S. Students in Higher Education through Virtual Exchange - Poe, Janita (Journal of International Students, 2022)
The celebration of diversity is at the heart of global education initiatives. Yet, participation in study abroad and related programs in the United States – a purported ‘melting pot’ of races and cultures – remains, disproportionately, the domain of affluent whites. Against this background, this study seeks to learn from the experiences of underrepresented and hypersegregated students in international virtual exchange, an educational experience involving sustained interaction between geographically separated participants using technology and trained facilitators. Using a survey, semi-structured interviews, exchange field notes, and the researcher’s own abroad experiences, the data revealed five main themes: ‘Virtual connections beyond the classroom,’ ‘Bias reduction,’ ‘Color matters,’ ‘Equality in digital space,’ and ‘One step closer to abroad.’ Findings suggest that U.S. universities and other educational institutions serving underrepresented groups can increase student international experiences by promoting IVE on their campuses and encouraging professors to include exchange as a component in their courses.